Clinical Study of Characteristics of Acute Poisoning Caused by Calcium Channel Blockers - LI Hui, REN Zhen, GUO Zhiguo (Zhongguo quanke yixue, 2023)
Background Calcium channel blockers (CCBs) are the most commonly used class of antihypertensive drugs in China. Despite the high mortality rate of severe CCBs poisoning, few relevant reports on its clinical characteristics can be found currently. Objective To analyze the clinical characteristics of acute CCBs poisoning and the value of blood purification therapy by summarizing the clinical manifestations and treatment results of 11 patients with acute CCBs poisoning. Methods A retrospective analysis was conducted with regard to the clinical presentation, scores for condition assessment, treatment process and prognosis of 11 patients who presented to the Emergency Department, Peking University Third Hospital for acute CCBs poisoning from January 2019 to June 2022. Results Of the 11 patients, 3 were female and 8 were male. The average age was (39.8±18.0) years and the median interval between drug administration and consultation was 2.25 (6.58) hours. The main clinical manifestations at presentation were shock (9 cases, 9/11) , nausea and vomiting (5 cases, 5/11) , dizziness (4 cases, 4/11) , fatigue (3 cases, 3/11) , tachycardia (3 cases, 3/11) , bradycardia (2 cases, 2/11) , syncope (1 case, 1/11) and lethargy (1 case, 1/11) . Ten patients arrived at the ED with a clear consciousness (with a Glasgow Coma Score of 15 points) . In addition to conventional treatment, 6 of the patients received blood purification treatment, including hemoperfusion, plasma exchange and continuous veno-venous hemofiltration (CVVH) in 2 cases, hemoperfusion combined with CVVH in 2 cases, and hemoperfusion alone in 2 cases. Four of these 6 patients also received extracorporeal membrane pulmonary oxygenation therapy. The blood concentration of CCBs decreased after the first blood purification treatment, and the percentage of decrease was higher for nifedipine (40.00%-63.64%) than for amlodipine and verapamil (9.09%-26.67%) . Nine of the 11 patients survived at discharge. The median Acute Physiology and Chronic Health Evaluation (APACHEⅡ) score at admission was 10 (25) points. The median Poisoning Severity Score (PSS) at admission was 3 (1) points. Two of the 8 patients with a PSS score of 3 points at admission died, and two of the 5 patients with an APACHEⅡ score ≥15 points at admission died. Conclusion Clarity of consciousness at the early stage of shock is a more common manifestation of acute CCBs poisoning. Hemoperfusion may play a more effective role in acute nifedipine poisoning than in acute amlodipine and verapamil poisoning. The APACHEⅡ score may be superior to the PSS score in predicting the prognosis of death in acute poisoning of CCBs.